The kingdom of power : how to demonstrate it here & now - Maldonado, Guillermo (New Kensington, PA : Whitaker House, 2013)
"The kingdom of God is His will exercised on earth as it is in heaven by the power of the Holy Spirit working through His people to produce tangible, supernatural manifestations of the kingdom, such as miracles, signs, healings, and deliverance"--Provided by publisher.
Keywords: Kingdom of God; God (Christianity); Supernatural